2011
DOI: 10.2474/trol.6.123
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydrogen on Microstructural Change and Surface Originated Flaking in Rolling Contact Fatigue

Abstract: The effects of hydrogen on microstructural change and surface originated flaking in rolling contact fatigue were investigated using JIS-SUJ2 bearing steel specimens charged with hydrogen. Under clean lubrication conditions, subsurface originated flaking occurred and the rolling contact fatigue life was reduced and the amounts of the microstructural change called white structure that formed in the specimens increased as the hydrogen content increased. The localized microstructural changes were found in the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 26 publications
3
77
0
Order By: Relevance
“…This will cause serious problems in critical components such as bearings [4][5][6][10][11][12][13][14][15][16]. Uyama et al [6] and Ciruna et al [3] observed that hydrogen content in the AISI 52100 bearing steel is one of the prime reasons for reduced bearing life. They found that fatigue life of AISI 52100 bearing steel ball is inversely related to the hydrogen content in the steel.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This will cause serious problems in critical components such as bearings [4][5][6][10][11][12][13][14][15][16]. Uyama et al [6] and Ciruna et al [3] observed that hydrogen content in the AISI 52100 bearing steel is one of the prime reasons for reduced bearing life. They found that fatigue life of AISI 52100 bearing steel ball is inversely related to the hydrogen content in the steel.…”
Section: Introductionmentioning
confidence: 99%
“…They correlated the reduction of fatigue life of the bearing steel (from 10 6 to 10 3 revolutions) with presence of 4 ppm hydrogen in the steel. Uyama et al [6] proved that increasing hydrogen content in the steel from 0.03 mass-ppm to 1.2 mass-ppm, decreases steel fatigue life more than one order of magnitude. They pointed out that the shorter life of hydrogen-charged samples is due to the acceleration of the localised microstructural changes under rolling contact fatigue tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanical properties of SUJ2 were reported to deteriorate due to rolling contact fatigue induced by hydrogen. 1,2) A white etching area (WEA) was observed on the fracture surface due to rolling contact fatigue, which was presumably associated with hydrogen embrittlement. In experiments to reproduce WEA in rolling contact fatigue tests, it was reported that WEA formation was associated with phase transformation of the retained austenite phase (γ R ), with the result that a number of voids were formed on the interfaces between martensite and γ R .…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, previous studies have showed the RCF would reduce the life and reliability of many useful components, such as gears, rolling bearings [4][5][6]. Nagao M find the stiffness of an inclusion and its location have a significant effect on the RCF life, stiffer inclusions and inclusions located at the depth of maximum shear stress reversal are more detrimental to the RCF life [7].T.Karsch studied the effects of hydrogen content and microstructure on fatigue behavior of steel GCr15 in the VHCF regime [8],and it is found that increased hydrogen content in bearing steel at 5 ppm (by weight) will significantly promote bearing spalling failure [9,10]. Shigeo shmizu's studies show that the bearing fatigue life is directly related to the instantaneous contact time, with the increase of the instantaneous contact time, the fatigue life is also increased [11].…”
Section: Introductionmentioning
confidence: 99%